Tir Is Essential for the Recruitment of Tks5 to Enteropathogenic Escherichia coli Pedestals - Jensen, Helene H. (PLoS One, 2015)
Enteropathogenic Escherichia coli (EPEC) is a bacterial pathogen that infects the epithelial lining of the small intestine and causes diarrhea. Upon attachment to the intestinal epithelium, EPEC uses a Type III Secretion System to inject its own high affinity receptor Translocated intimin receptor (Tir) into the host cell. Tir facilitates tight adhesion and recruitment of actin-regulating proteins leading to formation of an actin pedestal beneath the infecting bacterium. The pedestal has several similarities with podosomes, which are basolateral actin-rich extensions found in some migrating animal cells. Formation of podosomes is dependent upon the early podosome-specific scavenger protein Tks5, which is involved in actin recruitment. Although Tks5 is expressed in epithelial cells, and podosomes and EPEC pedestals share many components in their structure and mechanism of formation, the potential role of Tks5 in EPEC infections has not been studied. The aim of this study was to determine the subcellular localization of Tks5 in epithelial cells and to investigate if Tks5 is recruited to the EPEC pedestal. In an epithelial MDCK cell line stably expressing Tks5-EGFP, Tks5 localized to actin bundles. Upon infection, EPEC recruited Tks5-EGFP. Tir, but not Tir phosphorylation was essential for the recruitment. Time-lapse microscopy revealed that Tks5-EGFP was recruited instantly upon EPEC attachment to host cells, simultaneously with actin and N-WASp. EPEC infection of cells expressing a ΔPX-Tks5 deletion version of Tks5 showed that EPEC was able to both infect and form pedestals when the PX domain was deleted from Tks5. Future investigations will clarify the role of Tks5 in EPEC infection and pedestal formation.